2016
DOI: 10.1098/rsos.160499
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary implications of interspecific variation in a maternal effect: a meta-analysis of yolk testosterone response to competition

Abstract: Competition between conspecifics during the breeding season can result in behavioural and physiological programming of offspring via maternal effects. For birds, in which maternal effects are best studied, it has been claimed that exposure to increased competition causes greater deposition of testosterone into egg yolks, which creates faster growing, more aggressive offspring; such traits are thought to be beneficial for high-competition environments. Nevertheless, not all species show a positive relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 124 publications
1
21
0
Order By: Relevance
“…v 2 , F, t, z, OR) into r (Wolf 1986;Borenstein et al 2009;Aloe & Thompson 2013). When test statistics were not reported, we simplified binary infection status to a contingency table and determined v 2 , calculated the standardised mean difference (Cohen's d) for intensity, or converted the p value to a standard normal deviate Z-score and used n to obtain r (Bentz et al 2016). We assigned negative values to r when infection was lower for hosts in better condition (or when infected hosts had poorer condition) and converted directional r into Fisher's Z (Zr; Borenstein et al 2009).…”
Section: Assembling Condition-infection Datamentioning
confidence: 99%
“…v 2 , F, t, z, OR) into r (Wolf 1986;Borenstein et al 2009;Aloe & Thompson 2013). When test statistics were not reported, we simplified binary infection status to a contingency table and determined v 2 , calculated the standardised mean difference (Cohen's d) for intensity, or converted the p value to a standard normal deviate Z-score and used n to obtain r (Bentz et al 2016). We assigned negative values to r when infection was lower for hosts in better condition (or when infected hosts had poorer condition) and converted directional r into Fisher's Z (Zr; Borenstein et al 2009).…”
Section: Assembling Condition-infection Datamentioning
confidence: 99%
“…When the value of test statistic was not reported, we followed Bentz et al. () and used the reported p value and sample size to calculate r . We assigned negative values to effect sizes for which the garden attributes significantly decreased pollinators (Viechtbauer ).…”
Section: Meta‐analysis Of Garden Characteristics Effects On Pollinatorsmentioning
confidence: 99%
“…Despite this, little work has investigated the potential role of the developmental environment in influencing female–female competition and levels of aggression (though see Cain & Ketterson, ; Cain & Langmore, for two observational field studies in birds). Hormones experienced during development have been shown to influence levels of both juvenile and adult aggression in a variety of bird species (Bentz, Becker, & Navara, ; Cordero, Ansermet, & Sandi, ; Müller, Dijkstra, & Groothuis, ). One study in the spotted hyena ( Crocuta crocuta ) found that females exposed to higher levels of androgens during gestation displayed higher levels of aggression as cubs (Dloniak, French, & Holekamp, ), which acts as a good indicator of success in adult competition to acquire social rank, leading to higher reproductive success (Holekamp & Smale, ).…”
Section: Introductionmentioning
confidence: 99%